Developing a standardized approach to virtual clinic follow-up of hip and knee arthroplasty. (August 2019) - Preston, N.; McHugh, G. A.; Hensor, E. M. A.; Grainger, A. J.; O'Connor, P. J.; Conaghan, P. G.; Stone, M. H.; Kingsbury, S. R.
Abstract : Aims: This study aimed to develop a virtual clinic for the purpose of reducing face-to-face orthopaedic consultations. Patients and Methods: Anonymized experts (hip and knee arthroplasty patients, surgeons, physiotherapists, radiologists, and arthroplasty practitioners) gave feedback via a Delphi Consensus Technique. This consisted of an iterative sequence of online surveys, during which virtual documents, made up of a patient-reported questionnaire, standardized radiology report, and decision-guiding algorithm, were modified until consensus was achieved. We tested the patient-reported questionnaire on seven patients in orthopaedic clinics using a 'think-aloud' process to capture difficulties with its completion. Results: A patient-reported 13-item questionnaire was developed covering pain, mobility, and activity. The radiology report included up to ten items (e.g. progressive periprosthetic bone loss) depending on the type of arthroplasty. The algorithm concludes in one of three outcomes: review at surgeon's discretion (three to 12 months); see at next available clinic; or long-term follow-up/discharge. Conclusion: The virtual clinic approach with attendant documents achieved consensus by orthopaedic experts, radiologists, and patients. The robust development and testing of this standardized virtual clinic provided a sound platform for organizations in the United Kingdom to adopt a virtual clinic approach for follow-up of hip and knee arthroplasty patients. Cite this article: Bone Joint J 2019;101-B:951–959.